Age differences in perceptions of memory strategy effectiveness for recent and remote memory. Issue 2 (4th March 2018) - Lineweaver, Tara T.; Horhota, Michelle; Crumley, Jessica; Geanon, Catherine T.; Juett, Jacqueline J.
ABSTRACT: We examined whether young and older adults hold different beliefs about the effectiveness of memory strategies for specific types of memory tasks and whether memory strategies are perceived to be differentially effective for young, middle-aged, and older targets. Participants rated the effectiveness of five memory strategies for 10 memory tasks at three target ages (20, 50, and 80 years old). Older adults did not strongly differentiate strategy effectiveness, viewing most strategies as similarly effective across memory tasks. Young adults held strategy-specific beliefs, endorsing external aids and physical health as more effective than a positive attitude or internal strategies, without substantial differentiation based on task. We also found differences in anticipated strategy effectiveness for targets of different ages. Older adults described cognitive and physical health strategies as more effective for older than middle-aged targets, whereas young adults expected these strategies to be equally effective for middle-aged and older target adults.